Letter from William O'Brien to the Editor of the 'Irish Nation', William Patrick Ryan, informing him that he would like to purchase six shares in addition to the four already obtained in order to prevent the Irish Nation cease publication - O'Brien, William, 1881-1968; Ryan, W. P. (William Patrick), 1867-1942; The Irish Nation (Newspaper) 1909 (1909)
O'Brien writes of the Irish Nation "The Irish Nation, I believe, the most hopeful force in Ireland at present and if continued on its present tolerant and progressive lines must have an immense influence in shaping the thought and action of the missing Irish Democracy.".
Letter includes O'Brien's address as "43, Belvidere Place / Dublin".
Keywords: O'Brien, William, -- 1881-1968 -- Correspondence; Ireland -- History -- 1901-1910